Triggered star formation in a molecular shell created by a SNR? - Cichowolski, Silvina (2014)
We present a study of a new molecular shell, G 126.1-0.8-14, using available multiwavelength Galactic plane surveys and optical Gemini observations. A well-defined shell-like structure is observed in the CO(1-0) line emission at (l,b) = (126°.1, -0°.8), in the velocity range -10.5 to -15.5 km s-1. The H I emission shows a region of low emissivity inside G 126.1-0.8-14, while radio continuum observations reveal faint non-thermal emission possibly related to this shell. Optical spectra obtained with Gemini South show the existence of B-type stars likely to be associated with G 126.1-0.8-14. An estimate of the stellar wind energy injected by these stars shows that they alone cannot be able to create such a structure. On the other hand, one supernova explosionwould provide enough energy to generate the shell. Using the MSX, IRAS and WISE point source catalogues we have found about 30 young stellar object candidates, whose birth could have been triggered by the expansion of G 126.1-0.8-14. In this context, Sh2-187 could be a consequence of the action on its surroundings of the most massive (and thus most evolve) of the stars formed by the expanding molecular shell.